Find the general solution ?

enter image source here

1 Answer
Mar 20, 2018

See below.

Explanation:

Using the Laplace transform is handy

X = ((x_1),(x_2))
A = ((1,1),(-4,1))

dot X = A X rArr sX(s)= A X(s)+x_0 then

X(s) = (sI_2-A)^-1 x_0

here

(sI_2-A)^-1 =1/(s^2-2s+5) ((s-1,1),(-4,s-1))

and x_0 = (x_(10),x_(20)) are initial conditions.

then

X(s) = 1/(s^2-2s+5)(((s-1)x_(10)+x_(20)),(-4x_(10)+(s-1)x_(20)))

and

inverting

X(t) = ((x_1(t)),(x_2(t)))=((1/2(2cos(2t)x_(10)+sin(2t)x_(20))),(cos(2t)x_(20)-2sin(2t)x_(10)))e^t u(t)

here u(t) is the unitary step function.